Basal Cell Carcinoma Arising on a Verrucous Epidermal Nevus: A Case Report - Analia Viana; Felipe Aguinaga; Flauberto Marinho; Rosangela Rodrigues; Tullia Cuzzi; Marcia Ramos- (Karger Publishers, 2015)
We report a case of basal cell carcinoma that appeared from an epidermal verrucous nevus in a 61-year-old patient. The onset of basal cell carcinoma in sebaceous nevi, basal cell nevi and dysplastic nevi is relatively common, but it is rarely associated with epidermal verrucous nevi. There is no consensus on whether the two lesions have a common cellular origin or whether they merely represent a collision of two distinct tumors. Since this association - as with other malignant tumors - is rare, there is no need for prophylactic removal of epidermal verrucous nevi.